MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS I MENGGUNAKAN MEDIA GAMBAR SERI DI SDN 014 PENGALIHAN ENOK INDRAGIRI HILIR - Suyati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to improve students' writing skills through picture series media. This research was classroom action research which was believed to improve students' learning outcomes. The study was conducted at the first grade of SDN 014 Pengalian Enok. The subjects in this study were 29 students consisting of 12 male students and 17 female students. The results showed that picture series media improved students' writing skills. It was evident from the improvement of daily test results. The initial score of the students' daily test was 58, which was still below the KKM set by the school. Then, after the learning reflection on the first daily test, the average score of students' learning outcomes increased to 72. The students' scores increased by 12.4% compared to the initial data. Then, the average score on the second daily test also increased to 88, meaning that the students' learning outcomes increased by 15.6%. Therefore, using picture series media improved the students' writing skills at grade 1 of SDN 014 Pengalian Enok.